Review of Clinical Periodontology - Kumar Narayanaswamy Krishna; Jaypee eBooks (Jaypee Brothers Medical Publisher (P) Ltd., 2007)
This book mainly concentrates on exam related topics which allows students to prepare for the examination in very less time. Few chapters are explained in the form of flow charts which are easy to grasp. Subject matter of the book is in the form of points which help students to study, revise and recollect easily when required. Ascertain all readers that this book is a substitute to any of the standard textbooks.
Keywords: MCQs and Self-assessment,Periodontics; Electronic books